Features of liver damage in patients with coronavirus disease (COVID-19) with pneumonia in relation to indicators of inflammation taking into account oxygen dependence - Riabokon, O. V.; Kuliesh, I. O.; Рябоконь, Олена Вячеславівна; Кулєш, І. О. (My University, 2024)
Aim. The purpose of the work is to analyze the biochemical indicators of liver function in relation to indicators of inflammation in patients with coronavirus disease (COVID-19) with pneumonia, taking into account the development of oxygen dependence. Material and methods. 123 patients with COVID-19 with pneumonia were examined. The diagnosis was confirmed by isolation of RNA-SARS-CoV-2 from the nasopharyngeal mucus by polymerase chain reaction. The presence of pneumonia in all patients was confirmed by X-ray or computer tomography of the chest organs. The patients were divided into groups: I group – 32 patients with a moderately severe course without oxygen dependence; II group – 91 patients with a severe course with oxygen dependence. Exclusion criteria from the research were: the presence of infection with hepatotropic viruses and the presence of previously diagnosed other chronic liver diseases. Statistical data processing was carried out in the program Statistica for Windows 13 (StatSoft Inc., No. JPZ804I382130ARCN10-J). Results. In 45.5 % of patients with COVID-19 with pneumonia at the time of hospitalization by 9.0 [7.0; 12.0] days of the disease, liver damage with the development of cytolytic syndrome was confirmed. The frequency of liver damage in patients with COVID-19 with pneumonia increased with the appearance of oxygen dependence (25.0 % vs. 52.7 %, p = 0.007). Biochemical signs of the syndrome of intrahepatic cholestasis were weakly expressed, with the appearance of oxygen dependence, they were characterized by an increase the number of patients with an elevated level of gammaglutamyltranspeptidase (59.7 % vs. 24.0 %, p = 0.002) in the absence of statistically significant changes in the median indicators activity of gammaglutamyltranspeptidase and alkaline phosphatase (p > 0.05). The relationship between liver damage and the development of oxygen dependence in patients with COVID-19 with pneumonia is confirmed by the correlation between the activity index of alanine aminotransferase (ALT) and the oxygen saturation index (r = -0.31, p < 0.05). In patients with COVID-19 with pneumonia in the dynamics after a week in presence of oxygen dependence, a higher level of activity of ALT remained (p < 0.05) and the frequency of detection of increased activity of ALT remained higher (62.6 % vs. 37.5 %, χ2 = 6.07, p = 0.01), the activity of aspartate aminotransferase is higher (p < 0.05), compared to patients with COVID-19 with pneumonia without oxygen dependence. Мета роботи – проаналізувати біохімічні показники функції печінки у взаємозв’язку з показниками запалення у хворих на коронавірусну хворобу (COVID-19) та пневмонію, враховуючи розвиток кисневої залежності. Матеріали і методи. Обстежили 123 хворих на COVID-19 і пневмонію. Діагноз підтверджено виділенням RNA-SARSCoV- 2 із носоглоткового слизу методом полімеразної ланцюгової реакції. Пневмонію в усіх хворих підтверджено методом рентгенографії або комп’ютерної томографії органів грудної клітки. Хворих поділили на групи: І – 32 пацієнти з середньотяжким перебігом без кисневої залежності; ІІ – 91 пацієнт із тяжким перебігом і кисневою залежністю. Критерії виключення з дослідження – інфікування гепатотропними вірусами та раніше діагностовані інші хронічні хвороби печінки. Статистично дані опрацювали в програмі Statistica for Windows 13 (StatSoft Inc., № JPZ804I382130ARCN10-J). Результати. У 45,5 % хворих на COVID-19 із пневмонією на час госпіталізації на 9,0 [7,0; 12,0] дня хвороби підтверджено ураження печінки з розвитком цитолітичного синдрому. Частота ураження печінки у хворих на COVID-19 із пневмонією збільшувалася в разі виникнення кисневої залежності (25,0 % проти 52,7 %, р = 0,007). Біохімічні ознаки синдрому внутрішньопечінкового холестазу виражені слабо; в разі виникнення кисневої залежності зафіксовано збільшення кількості пацієнтів із підвищеним рівнем гамма-глутамілтрансферази (59,7 % проти 24,0 %, р = 0,002), при цьому не зафіксовано статистично значущих змін медіан показників активності і гамма-глутамілтрансферази, і лужної фосфатази (р > 0,05). Взаємозв’язок між ураженням печінки та розвитком кисневої залежності у хворих на COVID-19 і пневмонію підтверджує кореляція між показником активності аланінамінотрансферази (АлАТ) і рівнем сатурації кисню (r = -0,31, р < 0,05). За наявності кисневої залежності у хворих на COVID-19 і пневмонію в динаміці через тиждень вищим залишався рівень активності АлАТ (р < 0,05), а також частота виявлення підвищеної активності АлАТ (62,6 % проти 37,5 %, χ2 = 6,07, р = 0,01), зафіксовано вищу активність аспартатамінотрансферази (р < 0,05) порівняно з хворими на COVID-19 і пневмонію без кисневої залежності.
Особливості ураження печінки у хворих на коронавірусну хворобу (COVID-19) та пневмонію у взаємозв’язку з показниками запалення, враховуючи кисневу залежність
Keywords: coronavirus disease; COVID-19; pneumonia; oxygen dependence; liver damage; diagnosis; коронавірусна хвороба; пневмонія; киснева залежність; ураження печінки; діагностика